2006
DOI: 10.1017/s1092852900014371
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Physical Symptoms: A Common Manifestation of Psychiatric Disorders in Primary Care

Abstract: Worldwide, patients with common mental disorders, such as depression and anxiety, have a tendency to present first to primary care exhibiting idiopathic physical symptoms. Typically, these symptoms consist of pain and other physical complaints that remain medically unexplained. While in the past, traditional psychopathology emphasized the relevance of somatic presentations for disorders, such as depression, in the last few decades, the “somatic component” has been neglected in the assessment and treatment of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 72 publications
0
18
0
1
Order By: Relevance
“…Thinking too much was also shown to be a significant idiom of distress in depressed Zimbabwean women in (Patel, 1998). Some described somatic concerns not considered ICD-10 features of major depression, are shown to be common presentations of depression in primary care settings (den Boer et al, 2002;Escobar et al, 2006) and Kelly et al (2001) reported amplification of physical health symptoms in depressed pregnant women. Subjective accounts of difficulties in social role functioning (household chores, and social interaction) and personal grooming, provided context specific information on functional impairments to guide assessment of depression severity (WHO, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Thinking too much was also shown to be a significant idiom of distress in depressed Zimbabwean women in (Patel, 1998). Some described somatic concerns not considered ICD-10 features of major depression, are shown to be common presentations of depression in primary care settings (den Boer et al, 2002;Escobar et al, 2006) and Kelly et al (2001) reported amplification of physical health symptoms in depressed pregnant women. Subjective accounts of difficulties in social role functioning (household chores, and social interaction) and personal grooming, provided context specific information on functional impairments to guide assessment of depression severity (WHO, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Validated instruments assessing illness and treatment attitudes and beliefs [14,35,52,64], associated with adherence [65,66] in some studies but not in others [67,68], may better explain the influence of negatively biased response to neutral stimuli on adherence [69]. Larger studies would also assess the influence of acculturation [70] and ethnicity on locus of control, somatization [71], and health beliefs [72], as a confounding effect may better explain the relationship between the somatoform scale and adherence.…”
Section: Discussionmentioning
confidence: 99%
“…This category has been controversial ever since DSM-IV was released 1 and has prompted nu- merous calls from experts in the field to reconsider the category. These calls have ranged in scope from radical reformulation 2,3 to substantial revision [4][5][6][7][8][9][10][11][12][13][14] to merely modest refinement. [15][16][17][18] Characterized primarily by physical rather than psychological symptoms, most patients present in medical rather than mental health settings, and a somatoform diagnosis confronts the clinician with the often-difficult decision of whether to attach a psychiatric label to a person with somatic complaints.…”
Section: T He American Psychiatric Association's Diagnostic and Statimentioning
confidence: 99%